PENGEMBANGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK MENGGUNAKAN DESAIN DIDAKTIS PENDEKATAN TRANSACTIONAL READING - Oktavia Oktavia; Sugiatno Sugiatno; Agung Hartoyo (IAIN Pontianak, 2022)
This study aims to reveal the development of mathematical problem solving skills of vocational high school students using a didactic design with a transactional reading approach. The research method used is action research in the form of pedagogical action research. The data sources of this study were 30 subjects of class XII AKL students and the data were answer sheets from the pretest and posttest results of the mean material. The results showed the development of mathematical problem solving skills with a didactic design with a transactional reading approach in the material mean class XII. This can be seen from the achievement of indicators of mathematical problem solving ability on the students' pretest and posttest results. Students also become more confident in the results of their own answers, dare to ask questions and give opinions. The ability of students to solve mathematical problems before being given learning using the didactic design of the transactional reading approach in the material mean class XII is still low. This is evidenced by the results of the pretest of 30 students, only 11 students scored above 70 with an average of 64. Students' mathematical problem solving abilities after being given learning using a didactic design with a transactional reading approach in the material means class XII developed. This can be seen from the posttest results of 30 students, only 6 students scored below 70 with an average score of 82.5. The average difference between the students' pretest results and the posttest results was 18.5.